JARID ARRAES E SEUS CORDÉIS FEMINISTAS: O SOAR DE VOZES NEGRAS SILENCIADAS - LÍGIA CHAVES RAMOS DOS SANTOS (2023)
In this dissertation, I propose to perform a reading and critical analysis black feminist literary production entitled Heroínas negras Brasileiras em 15 cordéis (2017), cordelista, journalist, curator of the Ferina project and member of the black feminist movement born in Cariri, Jarid Arraes. Through a vision that seeks to describe Jarid’s feminist and black project, I highlight the propositions of Lugar de Fala (2017), the philosopher and activist of the black feminist movement Djamila Ribeiro, resignification made by black women in the conscious construction of their identity guidelines. For this, I am based on a black feminist perspective, based on conceptions of Quem tem medo do feminismo negro? (2018) by Djamila Ribeiro. In addition, through an eminently decolonial reading, “colorismo”, I also anchor myself in theories of Bell Hooks, Lélia Gonzalez, Sueli Carneiro, Grada Kilomba and Gayatri Spivak, addressing themes suchas re-signification of identity, racism and sexism, blackening of feminism, memory andthe black voice. Therefore, I will seek not to endorse the condition of subalternity and silencing, but through a black feminist theoretical cut, I deal with issues relevant to the literary representation of women, their voice and the recognition of their identity, as well as their intellectual projects. I will also address issues related to structural racism that demarcate the relations of coloniality of power. I will establish a dialogue between the intellectual projects and the Northeastern and feminist Jarid Arraes and Auritha Tabajara. In addition, I will highlight some works by the artist Rosana Paulino, with the intention of giving voice to women silenced by national historiography. The research is based on theoretical assumptions of Adiche (2019), Agamben (2009), Almeida (2021), Almeida apud. D'Olivo (2018), Hooks (2019), Hooks (2021), Bento (2022), Cabral, Lima Luiz e da Silva (2022), Carneiro (2019), Collins (2019), Diangelo (2018), Elliott, Brito and Almeida (2019), Gomes (2021), Goldstein (1985, Gonzales, Gonzales(2020), Gonzales (Gonzales), 2020 (Gonzales (Gonzales)), 2020), Gonzales (2020) (2020), Mignolo (2017), Mignolo (2003), Ribeiro (2017), Ribeiro (2018), Ribeiro (2019), Santana (2021), Spivak (2014), Tiburi (2021) e Wolterstorff (1980).